Penerapan Metode Transportasi Untuk Analisa Pengiriman Barang Pada PT Cargo Indonesia Medan - Togatorop, R.G. Frenton (Journal of Computing and Informatics Research, 2021)
Delivery of goods at this time has become an urgent need, because if there is no delivery of goods between regions, there will be inequality of needs in an area. Of course, the delivery of goods is also very important for a country, because the delivery of goods is one way to sell domestic products abroad, and of course this makes a country prosperous. The transportation problem is one of the methods of solving linear programming problems whose solution can be done by using the simplex method or by using special techniques called transportation technic whose solutions are more efficient. Least Cost method is a method that makes allocations based on the lowest cost. By using this method, it is easier for PT. Indah Cargo is in the process of delivering goods